Tourism Sector Development Strategy in North Maluku: A Case Study of Tidore Islands - Runtunuwu, Prince Charles Heston (AIBPM Publisher, 2020)
Tourism is one of the important things for a country, with tourism, a country or more specifically the Regional Government where the tourist object is located, receives income from the income of each tourist attraction. This study aims to identify and determine tourism objects that need to get a priority scale as a leading tourism to be developed; how the strategies that need to be formulated in the context of developing tourist objects in the City of Tidore Islands. The number of research samples was 70 people. The test tools used are analysis weighted product, simple linear regression, SWOT analysis. The results showed that: (1) the leading tourist attraction in the City of Tidore Archipelago is the Kie Kedaton Kie tourist attraction in the Tidore Sultanate, which is ranked 1; (2) service quality on visitor satisfaction shows that the level of service quality has a significant effect of 73.3% on visitor satisfaction at the Kie Kedaton Kie Sultanate of Tidore; (3) The strategy for developing the leading tourism objects in the City of Tidore Islands is as follows: (i). Improve the quality and quantity of human resources (HR) so that managers of tourist attractions are more optimal, (ii). Development of supporting facilities to build vacant land, which is governed by policies and development of investment marketing and tourism marketing, (iii). Collaborating with third parties (private) or community self-help parties, (iv). Increased promotion through print media and tourism social media in its development so as to attract investors, (v). Increasing the improvement of the development concept development program by following the era of globalization without reducing its historical value to attract visitors so that they are ready to face competition between tourist objects, (vi) Accelerating building activities that have been designed considering the approaching year-end and holiday period (vii) Increasing the quality of the workforce professionals in the management of tourist objects so as to reduce environmental damage due to arbitrary developments.